THE APPLICATION OF ARTIFICIAL INTELLIGENCE AND MACHINE LEARNING FOR DISEASE DIAGNOSIS AND PROGNOSIS IN MODERN HEALTHCARE - Ozod Abdusalomov; Ozod Oltibekov; Sardor Normamatov (Modern American Journals, 2025)
The rapid advancement of artificial intelligence (AI) and machine learning (ML) technologies has revolutionized modern healthcare, particularly in the fields of disease diagnosis and prognosis. This article explores the current applications of AI and ML in medical diagnostics, highlighting how these technologies improve accuracy, speed, and efficiency in detecting various diseases. It discusses the integration of AI-driven tools in imaging analysis, predictive modeling, and personalized treatment planning. Additionally, challenges such as data privacy, algorithmic bias, and the need for clinical validation are addressed. The article also examines future prospects and the potential of AI and ML to transform patient care, reduce healthcare costs, and enhance decision-making processes in clinical settings.
Keywords: Artificial intelligence, machine learning, disease diagnosis, prognosis, healthcare technology, medical imaging, predictive analytics, personalized medicine, clinical decision support, healthcare innovation.